Living benthic foraminifera from cold-water coral ecosystems in the eastern Alboran Sea, Western Mediterranean. Issue 9 (September 2021) - Stalder, Claudio; ElKateb, Akram; Spangenberg, Jorge E.; Terhzaz, Loubna; Vertino, Agostina; Spezzaferri, Silvia
Abstract: Benthic foraminifera (protists with biomineralized tests) coupled with geochemical proxies are used for the first time to characterize present oceanographic conditions occurring in cold-water coral ecosystems (CWC) in the eastern Alboran Sea (Brittlestar Ridge and Cablier Mound), western Mediterranean Sea. Quantitative data on living (stained) benthic foraminifera from 5 box cores retrieved during the MD194 cruise on the RV Marion Dufresne reveal that these organisms are more diverse in presence of corals, where more numerous ecological niches occur than they are in pelagic adjacent sediments. These data confirm that CWC can be considered as "diversity hotspots" also for benthic foraminifera. Geochemical characterization shows that these sediments contain relatively fresh (labile) organic matter but also a reworked refractory component. In particular, the total organic carbon and the δ 13 Corg values suggest that some of the organic matter may be a mixture of marine and reworked particulate organic matter, compared to typical values from temperate phytoplankton. The δ 15 N of the organic fraction suggests that important atmospheric N2 -fixation and degradation processes occur in the region. Finally, our results show that a more effective advection of freshly exported particulate organic matter from the surface waters occur at the mound top rather than at the mound base or off-mound allowing some coral colonies to survive on the top of mounds in this region. The mud layer covering the coral rubble debris may suggest that the Brittlestar Ridge is today exposed to siltation preventing the growth of corals at the mound base or off-mound. Abstract : Living foraminifera; Cold-water corals; Alboran Sea; Mediterranean.